Unraveling axonal mechanisms of traumatic brain injury - Victorio M. Pozo Devoto; Valentina Lacovich; Monica Feole; Pratiksha Bhat; Jaroslav Chovan; Maria Čarna; Isaac G. Onyango; Neda Dragišić; Martina Sűsserová; Martin E. Barrios-Llerena; Gorazd B. Stokin (Acta Neuropathologica Communications, 2022)
Abstract Axonal swellings (AS) are one of the neuropathological hallmark of axonal injury in several disorders from trauma to neurodegeneration. Current evidence proposes a role of perturbed Ca2+ homeostasis in AS formation, involving impaired axonal transport and focal distension of the axons. Mechanisms of AS formation, in particular moments following injury, however, remain unknown. Here we show that AS form independently from intra-axonal Ca2+ changes, which are required primarily for the persistence of AS in time. We further show that the majority of axonal proteins undergoing de/phosphorylation immediately following injury belong to the cytoskeleton. This correlates with an increase in the distance of the actin/spectrin periodic rings and with microtubule tracks remodeling within AS. Observed cytoskeletal rearrangements support axonal transport without major interruptions. Our results demonstrate that the earliest axonal response to injury consists in physiological adaptations of axonal structure to preserve function rather than in immediate pathological events signaling axonal destruction.